Structural Changes in the Surface of Red Blood Cell Membranes during Long-Term Donor Blood Storage - V. V. Moroz; A. M. Golubev; A. M. Chernysh; E. K., Kozlova; V. Yu. Vasilyev; O. E Gudkova; V. A. Sergunova; M. S. Fedorova (Общая реаниматология)
Objective: to study changes in the surface of red blood cell membranes of donor blood at the macro- and ultrastructural level during its storage for 30 days and to evaluate the functional state of the red blood cell membrane during the whole storage period. Material and methods. The investigation was conducted on human whole blood and packed red blood cells placed in the specialized packs containing the preservative CPDA-1, by using calibrated electroporation and atomic force microscopy and measuring plasma pH. Conclusion. The long-term, up to 30-day, storage of whole blood and packed red blood cells at 4°C was attended by lower plasma pH and increased hemolysis rate constant during calibrated electroporation and by the development of oxidative processes. The hemolysis rate constant was also higher in the packed red blood cells than that in the whole blood. On days 5—6, the membrane structure showed defects that developed, as the blood was stored, and caused irreversible cell membrane damage by day 30. Key words: donor blood, red blood cell membranes, atomic force microscopy.